Hybridization between Beluga (Huso huso) and Persian Sturgeon (Acipenser persicus) and their growth comparison - Pourkazemi, M.; Mohseni, M.; Nowruzfashkami, M.R.; Bahmani, M.; Taheri, A.; Yarmohammadi, M. (Iranian Fisheries Science Research Institute, 2007)
In order to evaluate the possible production of hybrids using two species of sturgeon; beluga (Huso huso) and Persian sturgeon (Acipenser persicus) a reciprocal crosses with three treatments and three replicates for each treatment was conducted. Reproduction normatives including number of eggs per gram, fertilization rate, survival rate, and also 32 mophmetric and merestic parameters of parents, hybrids and control groups were compared. Genetic analysis of hybrid was conducted using two methods of cytogenetic (chromosome preparation) and molecular (microsatellite) techniques. Histological analysis was performed for sexual gonad development. The growth comparison between hybrids and control fish was conducted in fiberglass tanks for 18 months. Fish were fed using pellets and biometric measurements were carried out 17 times during the study period. Means, analysis of variance, standard deviation, Duncan s test and percentage of hetrosis were calculated using Quatro Pro and SPSS programs. Significant differences were detected between beluga controls and hybrids (male beluga x female A. persicus) and between A. persicus controls and hybrids (male beluga x female A. persicus) regarding number of eggs per gram (P 0.003). However no significant differences were detected between the control groups and hybrids regarding fertilization rate at the four celled and 35 celled stages, number of larvae produced, mortality rate up to the onset of exogenous feeding and the number of larvae surviving (P 0.01). Growth rates differed in hybrid fish and fish in the control groups and highest weight increase at the end of the rearing period belonged to beluga control (975 ± 10 g) followed by hybrids produced by crossing female beluga with male A. persicus (840 ± 143 g), hybrids produced by crossing female A. persicus with male beluga (681.85 ± 281 g) and lowest growth increases belonged to the A. persicus control group (535.15 ± 131 g). Specific growth rate in the second and third six months of rearing in hybrids produced by crossing ...